Using ‘drawing exercise’ in organisational analysis - Breidahl, Karen; Seemann, Janne (Tidsskrift for Arbejdsliv, 2009)
The article presents a data generation method for studying organisations. The method is named ‘drawing exercise’ and is meant as a contribution to develop methodological aspects of the focus groups interview. The method lets employees in a focus group setting present their ‘organizational everyday perceptions’ by using figurative expressions as new ways of making a number of agenda items visible that can otherwise be difficult to express by using only words and concepts. Though inspired by psychotherapy and G. Morgan the ‘drawing exercise’ foremost functions as the researcher’s diagnostic tool and not least as a generator for dialogue. Based on a case study of one of the 91 jobcentres in Denmark it is exemplified how simple drawings, done by employees at a work seminar, can capture fundamental problems and issues related to the organization and its processes.